2016
DOI: 10.1115/1.4034417
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rotor Casing on Low-Pressure Steam Turbine and Diffuser Interactions

Abstract: The present study aims to investigate the interaction between a last-stage steam turbine blade row and diffuser. This work is carried out using computational fluid dynamics (CFD) simulations of a generic last-stage low-pressure (LP) turbine and axial–radial exhaust diffuser attached to it. In order to determine the validity of the computational method, the CFD predictions are first compared with data obtained from an experimental test facility. A computational study is then performed for different design confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Based on the understanding of the flow interaction between the axial turbine and the exhaust volute, Singh et al 26 performed the computational study of the flow fields for different design configurations of diffusers with different turbine rotor casing contours, and the study mainly focused on the typical flow features such as effects of rotor tip leakage flows and subsequent changes in the rotor-diffuser flow interactions. The computational results further suggested that the rotor casing shape influences the turbine rotor work extraction capability and yields significant improvement in the static pressure recovery.…”
Section: Effect Of Coupled Turbine-volute Steady Interaction On Its Aerodynamicsmentioning
confidence: 99%
“…Based on the understanding of the flow interaction between the axial turbine and the exhaust volute, Singh et al 26 performed the computational study of the flow fields for different design configurations of diffusers with different turbine rotor casing contours, and the study mainly focused on the typical flow features such as effects of rotor tip leakage flows and subsequent changes in the rotor-diffuser flow interactions. The computational results further suggested that the rotor casing shape influences the turbine rotor work extraction capability and yields significant improvement in the static pressure recovery.…”
Section: Effect Of Coupled Turbine-volute Steady Interaction On Its Aerodynamicsmentioning
confidence: 99%